Decreasing the harmonic number of AC-DC converters for power quality - (:unkn) unknown (IEEE, 2003)
The AC supply voltage generated by the generating station has only the fundamental component of sinusoidal voltage. An ideal load should take only sinusoidal current form the supply for optimum use of energy generated. Whatever frequency of current drawn from the mains will reduce total power quality which is undesirable. This paper presents AC-DC converter effects on the quality of input power supply and explain effective solution to overcome them.
Keywords: power quality; harmonic; electromagnetic interference (EMI); rectifier; ripple reinjection